APPROACH TO THE NATURAL ENVIRONMENT (PLAS) TO IMPROVE SCIENCE LEARNING OUTCOMES - Fazriah, Annisa; Nurhasanah, Aan; Prasetio, Pajar Anugrah (PROGRES PENDIDIKAN, 2024)
The background to this research is that there is a problem of low learning outcomes for class V students in science content which is caused by the use of less varied learning approaches. The research method used in this research is quasi-experimental with a Non-Equivalent Control Group Design.  research menggunakan soalmultiple choice tests and observation sheets.  Based on statistical testing, namely the t test on the final test ( posttest ) data, it was obtained that Tvalue 2.31<T table 3.29, so the hypothesis was accepted, meaning that there were differences in learning outcomes for classes that used the PLAS approach and classes that used the conventional approach. Based on the results of the N-Gain test, it is known that the experimental class test results before the PLAS approach ( pretest ) were given an average score of 44.13. Meanwhile, the test result after being given the PLAS approach treatment ( posttest ) was 81.30. Then we get an N-Gain result of 0.648, so according to the N-Gain criteria, this result can be stated as a medium criterion. Meanwhile, the test results in the control class carried out before using the PLAS approach ( pretest ) obtained a score of 42.05. After being given treatment it became 59.55. And obtained an N-Gain result of 0.295, according to the N-Gain criteria, this result is stated as low criteria. The results of this research show that the application of the natural environment approach (PLAS) can improve students' science learning outcomes.